(Re) purposing identity in African literatures : a post-colonial analysis of Nadine Gordimer's selected novels - Montle, Malesela Edward (University of Limpopo, 2022)
This study sought to repurpose identity in African literatures with reference to Nadine Gordimer’s novels. The selected novels of Gordimer focus on the post-colonial background of Africa. The advent of colonialists in Africa occasioned a major shift of identities in the continent. It is the contact between Africa and the West that engendered African identity-crisis. This qualitative study which has been predicated on post-colonial theory, Afrocentricity, and feminism aimed to crystalise the issues that come to grips with identity in the post-colonial African context. Chapter one of the study has outlined the background and motivation, which among other things, probes into the issue of identity in Africa. The coloniser moulded African identities with Western influence. Hence the birth of Anglophone, Francophone and Lusophone African literatures. Moreover, chapter two has examined the shift of identity in Africa from the pre-colonial to the colonial and post-colonial backgrounds. This noted, African identity has undergone great transitions. The Western culture during the colonial and post-colonial African periods rose to predominance and appears to have a perennial influence on the future of Africa. Thus, the question of who an African is today has a complex answer. Many scholars have questioned the authenticity of defining African identity based on skin colour, language and birth. Chapters three, four and five have examined the theme of identity in Gordimer’s novels. Gordimer is one of the most established specialists of identity and her sampled novels for this study have reflected on Africa’s search and acquisition of post-colonial identity. Furthermore, Chapter six concluded that Gordimer’s novels have satisfactorily delineated the hurdles that menace Africa’s acquisition of a democratic identity such as the remnants of colonialism, which necessitate a robust decolonisation process. The chapter has also recommended that measures such as the rainbow project in (South) Africa should be embraced to break racial boundaries that oppose Africa’s acquisition of a democratic identity.
Thesis (Ph.D (English Studies) -- University of Limpopo, 2022
Keywords: Afrocentricity; African literature; Colonialism; Feminism; Identity; Post-colonialism; African literature; Authors, African; African literature -- Appreciation -- Africa; African literature -- History and criticism; Post-apartheid era -- Africa; Feminism -- Africa.; Feminism -- Africa -- History -- 19th century.